Flow Management with Differentiated Classes of Service and Quality of Experience - João Silva; João Ponte; João Pedro Lopes; Nuno Souto (Journal of Computer Networks and Communications)
Recently, mobile networks have been overloaded with a considerable amount of data traffic. This paper proposes a brokerage service for mobile environments, using policies and quality metrics and ensuring better usage of network resources with more fine-grained management based on flows, and expands previous work (Silva, et al.) with the novel addition of differentiated classes of service. A closed innovative control loop included in a flexible brokerage service in the network, as well as agents at the mobile terminals, detects and counteracts an abnormal data load in any access technology. This allows the terminals to make well-informed decisions about their connections to improve the number of connected flows per technology and the individual service level offered to each flow. Simulation results indicate that the current proposed management solution optimizes the usage of available 4G/5G network resources among a high number of flows in several usage scenarios where the technologies are extremely overloaded, while at the same time, protecting the higher classes of service.